Hypovolemic Status in Older Hip Fracture Patients Elucidated by Preoperative Transthoracic Echocardiography - Yasuhiro Watanabe; Toru Kaneda (Anesthesiology Research and Practice)
Older patients undergoing hip fracture surgery often experience intraoperative hemodynamic instability despite maintaining cardiac function. Although preoperative hemodynamics in such patients have been demonstrated mainly through invasive monitoring, few studies have addressed hemodynamics based on noninvasively measured parameters. We aimed to investigate preoperative hemodynamic states in older hip fracture patients using transthoracic echocardiography (TTE). The TTE data of patients aged >75 years who underwent hip fracture surgery or elective total hip arthroplasty (THA) between April 1, 2019, and March 31, 2021, were collected. In addition to the baseline characteristics, the TTE data from hip fracture patients were compared with the data of those who underwent THA. The hip fracture patients (n = 167) were significantly older and had lower stroke volume (45.6 vs. 50.9 ml; p<0.01) and stroke index (33.7 vs. 36.6 ml/m2; p<0.01) compared to those who underwent elective THA (n = 44). However, the cardiac output (3.51 vs. 3.48 L/min; p=0.273) and cardiac index (2.6 vs. 2.47 L/min/m2; p=0.855) for both groups were almost identical due to the increase in heart rate in the hip fracture group. Regarding other parameters including ejection fraction, fractional shortening, E/E′, and inferior vena cava diameter, there were no significant differences between the two groups. Our noninvasive TTE investigations suggested that hip fracture patients were volume-depleted, and the hypovolemic status activated the sympathetic nervous system, compensating for their cardiac output. Anesthesiologists must focus on the TTE-assessed parameters reflecting the volume status along with the cardiac function.